Claw sign of brachial plexopathy on 18F-FDG PET/CT in neurolymphomatosis following successful treatment of lymphoma - Simon Doran; Gerard Lambe; Afshin Nasoodi (European Journal of Hybrid Imaging, 2022)
Abstract Neurolymphomatosis is a rare neurological manifestation associated with non-Hodgkin’s lymphoma. Here we present a case of brachial plexus neurolymphomatosis in a patient with relapsed non-Hodgkin’s lymphoma exquisitely demonstrated on 18F-FDG PET/CT. It highlights the characteristic imaging features and importance of multimodality imaging in diagnosing neurolymphomatosis.